Starania o niemożliwe. Problemy wykonania przez stronę sowiecką postanowień traktatu ryskiego w sprawach finansowych - Wołos, Mariusz (1968– ) (Instytut Historii PAN, 2024)
The article aims to present the questions related to the Soviet implementation of the provisions of the Treaty of Riga regarding financial matters. In particular, these claus-es related to the payment of compensations for the active participation of the lands of the Republic of Poland in the economic life of the former Russian Empire, the re-evacuation of state railway assets to Poland, and, fi nally, the return of property of local government bodies, municipal boards, institutions, natural and legal persons. In addition, there was the question of the settlement of liabilities owed or donated to Polish citizens’ physical funds and capital.
p. 219-241
Summary in English.
Keywords: Polish-Soviet relations, 1918–1939; Treaty of Riga (1921); financial claims